2D MOF-derived porous NiCoSe nanosheet arrays on Ni foam for overall water splitting. Issue 1 (24th November 2020) - Zhou, Yue; Chen, Yanli; Wei, Maobin; Fan, Hougang; Liu, Xiaoyan; Liu, Qianyu; Liu, Yumeng; Cao, Jian; Yang, Lili
Abstract : A novel 2D porous NiCoSe nanosheet arrays were grown on Ni foam using ZIF-67 as precursors, which exhibited outstanding bifunctional electrocatalytic activity and superior durability for overall water splitting. Abstract : The exploitation of low-cost, efficient and stable electrocatalysts for overall water splitting in alkaline media is critical for future renewable energy systems, yet still remains a great challenge. Herein, we report the in situ growth of porous NiCoSe nanosheet arrays derived from 2D MOFs on Ni foam through a simple ion-exchange reaction followed by a hydrothermal process. Benefiting from the unique 2D multi-porous framework with high electrochemical active surface area, conductivity and open channels for the release of gaseous products, the as-prepared NiCoSe nanosheet arrays exhibit excellent electrochemical activity with a low overpotential of 170 mV for the hydrogen evolution reaction (HER) at 10 mA cm −2 and 278 mV for the oxygen evolution reaction (OER) at 20 mA cm −2 and long-term stability. Furthermore, the full cell only requires 1.51 V to drive the current density of 10 mA cm −2 when the NiCoSe nanosheet arrays are used as both anode and cathode, which also exhibits distinguished durability for over 48 h. The present work presents a general strategy for the rational design and synthesis of multifunctional 2D porous electrocatalysts, which is also expected to extend to other noble-metal-free catalysts.